(untitled) (Canadian Journal of Counselling and Psychotherapy, 2020)
This study explores Canadian clinicians’ perceptions of test feedback (TFB) and how those perceptions influence their practice. This secondary analysis of open-ended qualitative data extends a previous study with similar research questions conducted by Jacobson et al. (2015). A case study design and consensual qualitative research (CQR) data analysis procedure was utilized to enhance the trustworthiness of the results. The findings indicate that clinicians give TFB in a variety of settings. Clinicians emphasize the importance of providing tailored and collaborative TFB, of attending to ethical issues related to TFB, and of improving academic training in TFB. Also, clinicians discuss unique situations in which feedback is provided to a third party rather than to the testing individual. Clinical implications such as increased practical training for providing TFB are discussed. Future research could investigate the outcomes of TFB provision.